Human embryonic stem cells and derived contractile embryoid bodies are susceptible to Coxsakievirus B infection and respond to interferon Iβ treatment - Scassa, María E. (2011)
We studied the susceptibility of human embryonic stem cells and derived contractile embryoid bodies from WAO9, HUES-5 and HUES-16 cell lines to Coxsackievirus B infection. After validating stem cell-like properties and cardiac phenotype, Coxsackievirus B receptors CAR and DAF, as well as type I interferon receptors were detected in all cell lines and differentiation stages studied. Real-time PCR analysis showed that CAR mRNA levels were 3.4-fold higher in undifferentiated cells, while DAF transcript levels were 2.78-fold more abundant in differentiated cultures (P<0.05). All cell lines were susceptible to Coxsackievirus serotypes B1-5 infection as shown by RT-PCR detection of viral RNA, immunofluorescence detection of viral protein and infectivity titration of cell culture supernatants resulting in cell death. Supernatants infectivity titers 24-48h post-infection ranged from 105-106 plaque forming units (PFU)/ml, the highest titers were detected in undifferentiated cells. Cell viability detected by a colorimetric assay, showed inverse correlation with infectivity titers of cell culture supernatants. Treatment with 100 U of interferon Iβ significantly reduced viral replication and associated cell death during a 24-48 h observation period, as detected by reduced infectivity titers in the supernatants and increased cell viability by a colorimetric assay, respectively. We propose human embryonic stem cell and derived contractile embryoid bodies as a valid model to study cardiac Coxsackievirus B infection.